Hubungan antara Persepsi Dukungan Guru dan Resiliensi Akademik pada Remaja Prasejahtera di Jabodetabek - Marcelina Marcelina (Humanitas (Jurnal Psikologi), 2024)
This research aims to find the correlation between perceived teacher support and academic resilience in low income adolescents students in Jabodetabek. The author used two measuring instruments, namely Teacher as Social Context Questionnaire (Student Version) used to determine students' perceptions of teacher support, namely involvement support, structure support and autonomy support. Academic Resilience Scale (ARS-30) developed by Cassidy to measure academic resilience and consists of perseverance, reflecting and adaptive help-seeking and negative affect and emotional responses components. The number of respondents in this study amounted to 152 from junior and senior high school students with low income family backgrounds in Jabodetabek. The results showed that all components of teacher support had a positive and significant correlation with all components of academic resilience.